The Effect of Financial Incentives on Retirement Decision Making under Different Schemes of Information Provision: Experimental Evidence - Matthias Nicolas Giesecke; Guanzhong Yang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We elicit preferences for retirement timing under two schemes of financial incentives and across information treatments. Individuals are repeatedly asked to decide whether to retire immediately or to continue working in the setting of a laboratory experiment. We alternate two treatment parameters: First, we compare two schemes of financial incentives where the expected present value of pension wealth is either a declining or a constant function of the retirement age. Second, we change the amount of information regarding the expected pension wealth. In line with the common finding of the quasi-experimental literature, we find a considerable delay of retirement once benefit reductions make early retirement less attractive. The striking result is, however, that the amount of available information tremendously affects retirement decisions. Poorly informed individuals tend to make retirement decisions on the grounds of perceived reference points. Such decision criteria, e.g. social norms, may reduce the effectiveness of policies that aim at raising the retirement age.
Keywords: C91; H55; J26; 330